Per capita consumption, luxury consumption and the presidential puzzle: A partial resolution - Sean D. Campbell; Canlin Li (Brown University, Department of Economics, 2003)
Santa-Clara and Valkanov (2003) document that excess returns on the stock market are puzzlingly higher under Democratic presidential administrations. We examine whether differences in economic fundamentals can account for this presidential puzzle. We find that the role for fundamentals crucially depends on how they are defined. When fundamentals are identified with per capita consumption growth, differences in consumption growth account for at most 2% of the difference in excess returns across the presidential cycle. When fundamentals are identified with the consumption growth of luxury goods, as much as 45% of the difference in excess returns can be accounted for by differences in fundamentals. Other measures of macroeconomic economic performance indicate large differences in business cycle experience over the presidential cycle. Hence, large differences in excess returns coincide with large differences in economic fundamentals across the presidential cycle. We also investigate whether the observed difference in fundamentals and stock returns over the presidential cycle were anticipated over the period we study. We do this in two ways. First we examine real-time data on expectations. Expectations data reveal little evidence in favor of a systematic relationship between presidential party and expected fundamentals or stock returns. Secondly, we examine the robustness of the observed difference in stock returns and fundamentals to large, unpredictable macroeconomic shocks. Removing the influence of the most severe depression years and major military conflicts results in a considerable attenuation of the presidential puzzle. This finding supports the view that the differences in both fundamentals and excess returns over the presidential cycle were unanticipated.
Keywords: 330; Gesamtwirtschaftlicher Konsum; Luxusgut; Staatsoberhaupt; Politischer Konjunkturzyklus; USA